“ANALYSIS OF GRAPHITE/EPOXY/COCONUT COIR COMPOSITE MATERIAL USING FINITE ELEMENT METHOD IN COMPARISON WITH EXPERIMENTAL SOLUTION” (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this research paper composite material is manufactured by using hand layup method and mechanical properties are investigated. By using natural fibers with the epoxy and graphite fibers, the mechanical properties of the composite material show better results. Tensile strength and bending strength after testing found is very high as compared other composite material with natural fibers. At the end it is found that this graphite/ epoxy/ coconut coir composite material is feasible for the mechanical application. Also it is found that tensile and bending strength is high.